ANALISIS KESALAHAN SISWA KELAS VIII SMP NEGERI SATAP 1 TINOMBO SELATAN DALAM MENYELESAIKAN SOAL CERITA SISTEM PERSAMAAN LINEAR DUA VARIABEL BERDASARKAN METODE NEWMAN - SITTI ZAHRA; Gandung Sugita; Mustamin Idris; Anggraini Anggraini (Jurnal Elektronik Pendidikan Matematika Tadulako, 2025)
This study aims to describe the errors of grade VIII students at SMP Negeri Satap 1 Tinombo Selatan in solving story problems involving two-variable linear equation systems using the Newman method. Newman’s method identifies five types of errors: reading, understanding, transformation, process skills, and coding. This research employs a descriptive qualitative approach. The subjects include three students with different mathematical abilities: one high-achieving student (A), one medium-achieving student (T), and one low-achieving student (S). Data collection techniques involve written tests and interviews, with data credibility ensured through member checking. The data analysis process includes data condensation, data presentation, and conclusion drawing. The results indicate that none of the subjects experienced reading errors. However, all three made mistakes in understanding the problems. Subject T did not write what was asked in problem one and misidentified the question in problem two. Subject S also failed to state what was asked in problem two. All subjects struggled with transformation errors, mainly due to incorrect variable assignments. Subjects A and S made errors in problem two, while subject T also struggled with proper notation. Regarding process skills, subject A could not complete the division operation, subject T failed in algebraic manipulation in problem one and miscalculated multiplication in problem two, and subject S did not proceed to the next step. Finally, all three subjects made coding errors. Subjects A and S did not write conclusions, while subject T omitted and incompletely stated conclusions for problem two.